(untitled) (Research, Society and Development, 2021)
The hydrodynamic characterization of the solar-driven CO2 reforming of methane through b-SiC open-cell foam in a fluidized bed configuration is performed by reacting Methane (CH4) with carbon dioxide (CO2). The mathematical modelling is important to design and optimize the reforming methods. Usually, the reforming methods’s application through b-SiC foam bed improves the heat transfer and mass transfer due to high porosity and surface area of the b-SiC foam. Fluidized Bed Membrane (FBM) Reformers can be substantially studied as a promising equipment to investigate the thermochemical conversion of CH4 using CO2 to produce solar hydrogen. This work has as main objective a theoretical modelling to describe the process variables of the solar-driven CO2 reforming of methane in the FBM reformer. The FBM reformer is filled with b-SiC open-cell foam where the thermochemical conversion is carried out. The model variables describe the specific aims of work and these objectives can be identified from each equation of the developed mathematical model. The present work has been proposed to study two specific aims as (i) The effective thermal conductivity’s effect of the solid phase and (ii) molar flows of chemical components. The endothermic reaction temperature’s profiles are notably increased as the numeral value of the effective thermal conductivity’s effect of the solid phase. is rised. The solar-driven CO2 reforming method is suggested to improve the Production Rate (PR) of H2 regarding the PR of CO.